1992
DOI: 10.1246/bcsj.65.871
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ascorbic Acid on the Desorption of Gold in Graphite Furnace Atomic Absorption Spectrometry

Abstract: In the graphite furnace atomic absorption spectrometry of gold, signals with a single peak were observed with a pyrolytic graphite (PG) furnace, while signals with a shoulder on the tailing edge were observed with a nonpyrolytic graphite (NPG) furnace. A thermal shift of the atomic absorption signals for gold occurs in response to changes in the concentration of ascorbic acid without any loss for each furnace. When the pre-pyrolysis of a 5% (m/V) ascorbic acid solution was carried out at 1270 K, although the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…[25][26][27][28][29][30] In this study we investigated the atomization process of As using the enthalpy change (ΔH) at the atomization stage. Arsenic usually forms oxides at the pyrolysis stage in GFAAS and is atomized through the following processes:…”
Section: Atomization Mechanism Of As In Gfaas and Theoretical Enthalpmentioning
confidence: 99%
“…[25][26][27][28][29][30] In this study we investigated the atomization process of As using the enthalpy change (ΔH) at the atomization stage. Arsenic usually forms oxides at the pyrolysis stage in GFAAS and is atomized through the following processes:…”
Section: Atomization Mechanism Of As In Gfaas and Theoretical Enthalpmentioning
confidence: 99%
“…[3][4][5][6] Fonseca and co-workers 7 reported that vaporization of gold and silver appears to occur from varying sizes of microdroplets or from adatoms, depending on the analytical conditions, such as dry and thermal pretreatment conditions, chemisorbed oxygen on the graphite surface and mechanically created active sites on the graphite surface. In the case of silver, although a tendency of the activation energy (E a ) for atomization to increase as the concentration increases was observed with a fractional order desorption, a constant E a was observed below 0.06 ng of silver, which is in agreement with the morphology of dispersed atoms with a first order desorption.…”
mentioning
confidence: 99%
“…29 Arrhenius plots with a single slope were obtained for the Hf-, Ti-and Zr-treated PG furnaces. With the W-treated PG furnace, the first peak was observed as a small shoulder which was too small to deserve a kinetic analysis.…”
Section: Resultsmentioning
confidence: 99%